Alterações cromatínicas em espermatozoides de perus submetidos a dois níveis de proteína bruta na ração em três diferentes idades - Araújo, Daniel Santos (2013)
The present study aimed to evaluate the influence of age and protein level in the diet on the incidence of changes in condensation chromatin sperm of turkey, and also to evaluate the influence of these changes on the fertilizing capacity of sperm and embryonic development (hatching). Were used a total of 60 samples of semen turkeys, divided into 30 samples in group A: males fed diet P14 (14% protein) and 30 in group B: males fed diet P17 (17% protein). The semen was collected in the same flock when males had three different ages (37, 42 and 49 weeks) and collected 10 samples from each group at each age. All samples were divided in two aliquots which were stored at two different fixing solutions. For computer analysis of sperm chromatin condensation, one drop of semen was placed in 2 ml of formolcitrato solutions. For analysis by transmission electron microscopy, another drop of semen was placed in 2 ml of Karnovsky solution (2.5% glutaraldehyde, 2% paraformoldehyde; sodium phosphate buffer 0.1 M, pH 7.2). For staining was following the protocol that Rodrigues et al (2009) using staining with toluidine blue. Denaturation pre-staining with 1N hydrochloric acid for 10 minutes after completion of the semen smears on slides and dried at room temperature. The solution used for staining of toluidine blue in 0.025% pH4 in cuvettes for 20 minutes with subsequent dehydration in a series of increasing alcohol concentrations, cleared with xylene and assembly with Canada balsam oil. Digital images were captured, segmented to several heads of spermatozoa per program developed and evaluated in SCILAB:, perimeter, length, width, intensity and heterogeneity of chromatin compaction was used as the default value of the chromatin compaction bottom quartile of mean values the gray level of the heads analyzed in a single blade. Electron microscopy was used and the samples after processing were evaluated heads 100 of each sperm sample. The heads were classified by level of chromatin descompaction: normal, weak, medium and strong. The eggs were incubated and fertility rates and hatching were calculated. The staining protocol used allowed visual observation morphological changes, but the computational analysis was not considered reliable for lack of repeatability in the production of images and electron microscopy was considered very efficient and can be used as a technique for evaluating fertility in turkeys. The chromatin alterations observed by electron microscopy detracted fertility of turkey and hatching, because act in embryonic development. Beyond that feed content with 17% crude protein negatively affects fertility rates and hatching, where from 42-week-old turkeys are present more changes in chromatin structure.